Clinical characteristics of the primary hepatic malignant fibrous histiocytoma in China: case report and review of the literature - Yao Dianbo; Dai Chaoliu (World Journal of Surgical Oncology, 2012)
Abstract Background A malignant fibrous histiocytoma is a soft tissue tumor that most commonly occurs in the extremities, but rarely involves the liver. The clinical characteristics and therapeutic experiences of primary hepatic malignant fibrous histiocytoma are still limited. Methods Two cases of primary hepatic malignant fibrous histiocytoma were analyzed retrospectively, and all the literature concerning primary hepatic malignant fibrous histiocytoma was analyzed. Results In China, a total of 76 cases had been reported, among which 50 were men, with a male to female ratio of 1.9:1. Mean age of the patients was 51.0 years old, and more than 85 percent were older than 40 years. 82.9 percent (63/76) of hepatic MFH were solitary lesions, with tumor size ranging from 2.5 to 23.5 cm (average 10.3 cm). Major clinical presentation (78.4%) was abdominal pain or discomfort, accompanied with some other non-specific symptoms such as malaise, anorexia, weight loss, jaundice and fever, and small cases (14.9%) were asymptomatic. Computed tomography and ultrasound usually revealed the location of lesions. The rate of pre-operative misdiagnosis was extremely high, and 14.9 percent of patients were even misdiagnosed as a benign liver cyst, liver abscess or hematoma. Integrated resection was performed among the most cases (49/68), among which only a few ones (12 cases) were introduced to have no recurrence or metastasis or be still alive with no detail information provided, while among the cases with palliative operation or only a biopsy, the cases that were followed-up all died. Conclusions Hepatic malignant fibrous histiocytoma is a rare malignant mesenchymal tumor. The variable features of clinical presentations and images make the diagnosis difficult. Though the prognosis of primary hepatic malignant fibrous histiocytoma was rather poor, integrated resection might provide a few cases a good opportunity for surviving, suggesting that surgery might be an effective treatment.